The materiality of textiles and textile tools in the Late Bronze Age Eastern Mediterranean - Sauvage, Caroline (Archaeological Textiles Review, 2023)
This paper examines the materiality of Late Bronze Age Eastern Mediterranean (including the Aegean) textiles, fibres and textiles tools and aims to explore the relationship between people and their cloth and clothing while considering the diverse material properties of each garment and tool. It focuses on elite clothes and textiles. The article highlights the agency of matter and how the assemblage constituted by the individual elements of Late Bronze Age garments (natural fibres, imported or local dyes, colourful embellishments of beads, precious metals, and threads) acted on its environment as well as on its wearer. It also focuses on the meaning and information encoded both in garments and its constitutive parts and in textile tools. Clothes and textiles were actants who not only communicated to an audience, but also had the power to transfer and give energy, vitality, force, gender, status and identity to their wearer.